HCV treatment in Sardinian HIV-HCV coinfected patients: a real-life perspective study on safety, efficacy, and immune reconstitution. Issue 11 (2nd November 2022) - Pes, Francesco; Onali, Simona; Balestrieri, Cinzia; Angioni, Goffredo; Ortu, Francesco; Piano, Paola; Lucia, Barca; Scioscia, Rosetta; Princic, Elija; Bolliri, Anna Chiara; Casale, Michele; Cola, Alessandra; et al.
ABSTRACT: Background: HIV-HCV co-infected patients have long been considered difficult-to-treat. The introduction of direct-acting antivirals (DAAs) changed this paradigm.We evaluated the efficacy and safety of DAA-based regimens and the impact of DAAs-induced HCV clearance on the immunological status in HIV-HCV co-infected patients. Research design and methods: HIV patients starting HCV treatment with DAAs were included. Sustained virological response at 12 weeks after DAAs treatment (SVR12) was assessed. CD4+ and CD8+ blood cell count and CD4+/CD8+ ratio were recorded at baseline and six months post DAA treatment. We enrolled 201 patients, 76.1% males, median age 54 years, the most common genotypes 3 (29.8%) and 1a (29.4%), 40.3% with cirrhosis, 32.3% with prior interferon-based treatment. All patients were on antiretroviral treatment, 24.4% on methadone maintenance therapy and 22.6% on psychotropic drugs. Results: SVR12 was 98.4%, the most common side effects were pruritus (8.4%), headache (7.4%) and fatigue (5.9%). An increase in CD4+ and CD8+ cell count was observed six months after completion of DAAs treatment, in particular in patients with low CD4+ cell count at baseline. Conclusions: DAAs treatment resulted in high SVR12 rates, was well tolerated and Increased CD4+ and CD8+, especially in patients with low CD4+ cell count at baseline.